Development of Pedestrian Alert System for Use in Electric Vehicles - Nikola Frlić Sekulić; Ivan Blagojević; Vladimir Popović; Dragan Stamenković*; Slobodan Janković (Tehnički Vjesnik, 2019)
Modern technology has made electric vehicles more accessible, which is important for the preservation of the environment. Although eco-friendly, from the standpoint of pedestrian safety, they may be baleful. The low levels of noise emitted by electric vehicles at speeds lower than 20 km/h are not sufficient for the pedestrian to become aware of the approaching vehicle based on sound. The topic of this paper is the research of sounds used to warn pedestrians of an incoming electric vehicle, while the goal is to single out the most suitable applicable sound based on an unique self-developed multiparameter methodology (which has been experimentally proved). The paper contains the results of the experiments, both of selecting the most suitable applicable sound and driving-range testing.